Algorithm for the management of patients at low, high and very high risk of osteoporotic fractures - Kanis, J. A.; Harvey, N. C.; McCloskey, E.; Bruyère, O.; Veronese, N.; Lorentzon, M.; Cooper, C.; Rizzoli, R.; Adib, G.; Al-Daghri, N.; Campusano, C.; Chandran, M.; et al. (Osteoporosis international, 2020)
Summary Guidance is provided in an international setting on the assessment and specific treatment of postmenopausal women at low, high and very high risk of fragility fractures. Introduction The International Osteoporosis Foundation and European Society for Clinical and Economic Aspects of Osteoporosis and Osteoarthritis published guidance for the diagnosis and management of osteoporosis in 2019. This manuscript seeks to apply this in an international setting, taking additional account of further categorisation of increased risk of fracture, which may inform choice of therapeutic approach. Methods Clinical perspective and updated literature search. Results The following areas are reviewed: categorisation of fracture risk and general pharmacological management of osteoporosis. Conclusions A platform is provided on which specific guidelines can be developed for national use to characterise fracture risk and direct interventions.